Kandungan hidrogen cyanida (HCN), bahan kering, bahan organik umbi gadung (Dioscorea hispida dennst) menggunakan nira lontar dengan lama fermentasi yang berbeda: The content of hydogen cyanida (HCN), dry matter, organic matter from gadung tubers (Dioscorea hispida dennst) using palm sap with different fermentation - Redempta Wea; Adrianus Betu; Abner T. Lema; Bernadete B. Koten; Melkianus D. S. Randu (Fakultas Peternakan Universitas Papua, 2023)
Good pig productivity depends on the feed given. however, feed ingredients for pigs generally compete with human needs, so the use of alternative feeds for gadung tubers with fermentation technology needs to be done. The aim of the research to examine Hydrogen cyanida (HCN) levels, dry matter( DM), and organic matter (OM) of gadung tubers using lontar sap with different fermentation times has been carried out at the Kupang State Agricultural Polytechnic from May - June 2022. The design used a Completely Randomized Design (CRD) consisting of 5 treatment and 5 repetitions; P0: gadung tuber (GU) + fermented palm sap (FPS) 0 days, P1: GU + FPS 3 days, P2: GU + FPS 6 days, P3: GU + FPS 9 days, and P4: GU + FPS 12 days. The results showed that the use of 10% PS with different fermentation times affected the HCN, DM, and OM content of gadung tubers. It was concluded that the HCN, DM, and OM content of gadung tubers were affected by fermentation using palm sap at different times and the best time was 3 days. It is recommended to carry out further research on the effect of feeding gadung tubers using palm sap with different fermentation times on the palatability and growth of pigs